2010
DOI: 10.5694/j.1326-5377.2010.tb03530.x
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised controlled trial to prevent injury due to falls in a residential aged care population

Abstract: Objective: To test the effectiveness of using a full‐time project nurse to assist residential aged care facilities in using evidence‐based approaches to falls injury prevention. Design, setting and participants: Cluster randomised controlled trial involving 5391 residents in 88 aged care facilities in the Hunter and Lower Mid North Coast areas of New South Wales. Residents were followed for 545 days or until death or discharge. Data were collected from July 2005 to June 2007. Intervention: Employment of a proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 8 publications
0
59
0
1
Order By: Relevance
“…An a priori secondary subgroup analysis of one study showed that the effect was only significant in cognitively impaired residents (relative risk (RR) = 0.49, 95% confidence interval (CI) = 0.35–0.69) and not in cognitively intact residents (hazard rate (HR) = 0.91, 95% CI = 0.68–1.22). Pooled data from 10 studies showed no effect on number of falls (RR = 0.93, 95% CI = 0.76–1.13; I ² = 89.8%, P < .001) …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…An a priori secondary subgroup analysis of one study showed that the effect was only significant in cognitively impaired residents (relative risk (RR) = 0.49, 95% confidence interval (CI) = 0.35–0.69) and not in cognitively intact residents (hazard rate (HR) = 0.91, 95% CI = 0.68–1.22). Pooled data from 10 studies showed no effect on number of falls (RR = 0.93, 95% CI = 0.76–1.13; I ² = 89.8%, P < .001) …”
Section: Resultsmentioning
confidence: 97%
“…The number of falls was reported in 12 studies (Table ) . In nine studies, the intervention and control groups did not differ significantly in number of falls . Two multifactorial studies showed a significant decrease in falls of 36% and 45%, respectively, over a 12‐month period for the intervention groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note is that four trials that had been excluded in Cameron 2012 because they included participants with post-stroke hemiplegia, have now either been retracted (Sato 2000; Sato 2005a; Sato 2005b; see Retraction Watch) or, for Sato 2011, likely to be retracted in future because of serious concerns about research misconduct as revealed in Bolland 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have included exercise and other non-pharmaceutical interventions [6] to reduce falls and fall related injuries. There is evidence that fall prevention interventions reduce falls [6] but there is little evidence to support a reduction in fractures [7]; [8].…”
Section: Introductionmentioning
confidence: 99%